An Osteometric Analysis of Skeletons Excavated at Churchyards of Saint Mary Collegiate and of Saint Peter and Paul Church in Głogów (11th-14thc.) - Gronkiewicz, Stanisław (Anthropological Review, 1981)
Skeletal materials examined here belong to three samples (I, II, III) dated at a period between 11th and 14th century excavated during archeological-architectonic investigations carried in 1963-1971 on the outside (I) as well as within ruins (II) of St. Mary Collegiate and on the churchyard of St. Peter and Paul Church at Głogów (III). Total number of excavated skeletons is 76. For purposes of the present paper data on 41 skulls and 43 postcranial skeletons were analysed (tables 1-4). The skulls from Głogów vary from long (I) through intermediate (II) to short (III) in average values of cephalic index. Faces were either of medium breadth (I, II) or broad (III). Nasal indices fall into intermediate category (I, III) or that of narrow nose (II). Height of orbits was either small (I) or intermediate, (II, III). Braincases were low (I, II) and of medium height (III). Racial composition of the three series is shown in table 7. Comparison with other series of skeletal materials is illustrated by figure 1. Body height was reconstituted by means of Manouvrier’s method. It has been found that examined skeletons of medieval in habitants of Głogów belonged to persons of intermediate stature, though slightly shorter than in other Polish groups.